Drug-Drug Interaction between Warfarin and Alendronate Sodium in Elderly Patient: a Case Report - mahalavalert, sirikanya; boonkerng, Apinya (Journal of Health Science of Thailand, 2025)
While alendronate sodium is prescribed to mitigate the risk of bone fractures in older adults, it is crucial to be cognizant of its potential adverse effects. This is particularly important for elderly patients who have a history of one or more venous thromboembolism (VTE) events. The medication’s benefits must be carefully weighed against its risks in this vulnerable population. A 77-year-old female with a history of deep vein thrombosis (DVT), currently on warfarin, presented with spontaneous ecchymosis and was seen in the out- patient department. This patient had a prior hip fracture. She was diagnosed using the FRAX score, which indicated a 10-year probability of 35% for a major osteoporotic fracture and 23% for a hip fracture. The patient had been on long-term warfarin therapy due to her history of DVT. Alendronate sodium was prescribed to the patient at 70 mg once a week. Within one month, the patient experienced a provoked increase in international normalized ratio (INR) to 7.76, followed by a gradual decrease to 1.55 after the medication was stopped. The patient also developed spontaneous ecchymoses on the skin. In elderly female patients with osteoporosis and a history of DVT who are on warfarin therapy, alendronate sodium can cause significant increase in INR by over 50% and lead to spontaneous skin bruising. Healthcare providers should be caution when prescribing alendronate sodium to older adults already taking warfarin. It is crucial to be vigilant about the increased risk of bleeding complications that may arise from this drug interaction.